EKSPLORASI ETNOMATEMATIKA GERAK TARI GENJAH GUMIWANG KREASI KOMUNITAS SENI DAMAR ART BANYUWANGI - Agustina, Lady; Rahayu, Lusiana Dewi; Imamah, Nurul (TRANSFORMASI, 2025)
This study aims to describe the ethnomathematics of the floor pattern of the Genjah Gumiwang dance created by the Damar Art Community. This research is a qualitative  descriptive study with an ethnographic approach. Data collection was carried out using observation, interview, and documentation methods. Observations were made on the movements of the Genjah Gumiwang dance, while interviews were conducted with the dance choreographer. Data analysis was carried out with the stages of reduction, data presentation, and conclusion. The results indicate that the movements and floor patterns of the Genjah Gumiwang dance contain mathematical concepts: angles (acute angles, obtuse angles, straight angles, and right angles), flat shapes (trapezoids, parallelograms, and triangles), and transformation geometry (reflection). Furthermore, these results can be implemented in mathematics learning on relevant materials as a form of mathematical contextualization.